Soil contamination in arid environments and assessment of remediation applying surface evaporation capacitor model: a case study from the Judean Desert, Israel - R. Golan; I. Gavrieli; R. Katzir; G. Sharabi; U. Nachshon (SOIL)
Due to the presence of highly pollutant industries in arid areas, many of the globe's arid areas are exposed to severe local soil contamination events. In this work, the nature of solute and contaminant transport in the sandy terraces of an ephemeral stream that was exposed to a severe pollution event was examined. Here, the Ashalim Basin in the Judean Desert, Israel, is utilized as a case study.